2019
DOI: 10.3390/su11154035
|View full text |Cite
|
Sign up to set email alerts
|

The Spatial and Temporal Land Cover Patterns of the Qazaly Irrigation Zone in 2003–2018: The Case of Syrdarya River’s Lower Reaches, Kazakhstan

Abstract: In this study, the spatial and temporal patterns of the land cover were monitored within the Qazaly irrigation zone located in the deltaic zone of the Syrdarya river in the surroundings of the former Aral Sea. A 16-day MODIS (Moderate Resolution Imaging Spectroradiometer) Aqua NDVI (Normalized Difference Vegetation Index) data product with a spatial resolution of 250 meters was used for this purpose, covering the period between 2003 and 2018. Field survey results obtained in 2018 were used to build a sample da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 51 publications
0
4
0
Order By: Relevance
“…There are currently studies underway using RS and GIS data to study long-term changes in LULC in individual regions of the country. These works are devoted to the study of land-use changes outside the direct influence of urban sprawl [37][38][39][40] or only in the city itself [41]. At the same time, a comprehensive assessment of the impact of large cities of Kazakhstan on the surrounding agricultural areas using long-term spatiotemporal data series remains open for determining sustainable development approaches for both cities and PUAs.…”
Section: Introductionmentioning
confidence: 99%
“…There are currently studies underway using RS and GIS data to study long-term changes in LULC in individual regions of the country. These works are devoted to the study of land-use changes outside the direct influence of urban sprawl [37][38][39][40] or only in the city itself [41]. At the same time, a comprehensive assessment of the impact of large cities of Kazakhstan on the surrounding agricultural areas using long-term spatiotemporal data series remains open for determining sustainable development approaches for both cities and PUAs.…”
Section: Introductionmentioning
confidence: 99%
“…There are currently studies underway using GIT to study long-term changes in LULC in individual regions of the country. These works are devoted to the study of land-use changes outside the direct influence of urban sprawl [24][25][26][27]. At the same time, a comprehensive assessment of the impact of large cities of Kazakhstan on the surrounding agricultural areas using long-term spatiotemporal data series remains open for determining sustainable development approaches for both cities and PUAs.…”
Section: Introductionmentioning
confidence: 99%
“…As one of the two major rivers in Central Asia, research on the ecological environmental changes of the Syr Darya River, and its basin, has always been a hot spot of current research. Many fruitful studies have been carried out on climate change and surface water hydrological processes [14,15]; water resources and management [8,16,17]; land cover and irrigation suitability evaluation [18,19]; and soil degradation and its environmental effects [20][21][22]. Among them, Konstantinovna and Zheksembaevna [23], in the study of soil degradation in the basin, found that by investigating land cover changes in the modern delta of the Syr Darya River, from 1956 to 2008, that the trend of soil salinization was more pronounced due to the shrinking of the Aral Sea and the effects of aridification.…”
Section: Introductionmentioning
confidence: 99%